Foucault's critical ethics - Lynch, Richard A., 1967- (Just ideas., 2016)
Argues that Michel Foucault's account of power provides a inescapable framework for ethics. Traces Foucault's analyses of power and ancient and contemporary ethical practices. Articulates a Foucauldian ethics constituted by a critical attitude, with substantive but revisable values grounded in a practice of freedom.